Plásticos Forte S.A. - Mendiola, Alfredo (2002)
This is a case study in which a consultant analyzes the possibility of his client entering the Peruvian plastics market through a strategic alliance with Plásticos Forte a Peruvian capital company dedicated to the manufacture import and sale of plastic items. To this end the economic situation of Peru the plastics sector and the situation about Plásticos Forte company are analyzed.